Acute TMS/fMRI response explains offline TMS network effects – An interleaved TMS-fMRI study - M. Tik; M. Woletz; A.-L. Schuler; M. Vasileiadi; R.F.H. Cash; A. Zalesky; C. Lamm; C. Windischberger (NeuroImage, 2023)
Background: Transcranial magnetic stimulation (TMS) is an FDA-approved therapeutic option for treatment resistant depression. However, exact mechanisms-of-action are not fully understood and individual responses are variable. Moreover, although previously suggested, the exact network effects underlying TMS’ efficacy are poorly understood as of today. Although, it is supposed that DLPFC stimulation indirectly modulates the sgACC, recent evidence is sparse. Methods: Here, we used concurrent interleaved TMS/fMRI and state-of-the-science purpose-designed MRI head coils to delineate networks and downstream regions activated by DLPFC-TMS. Results: We show that regions of increased acute BOLD signal activation during TMS resemble a resting-state brain network previously shown to be modulated by offline TMS. There was a topographical overlap in wide spread cortical and sub-cortical areas within this specific RSN#17 derived from the 1000 functional connectomes project. Conclusion: These data imply a causal relation between DLPFC-TMS and activation of the ACC and a broader network that has been implicated in MDD. In the broader context of our recent work, these data imply a direct relation between initial changes in BOLD activity mediated by connectivity to the DLPFC target site, and later consolidation of connectivity between these regions. These insights advance our understanding of the mechanistic targets of DLPFC-TMS and may provide novel opportunities to characterize and optimize TMS therapy in other neurological and psychiatric disorders.